Dynamic Network Slicing for User Mobility Support in 5G Networks - Gonçalves, Diogo M.; Bittencourt, Luiz F.; Madeira, Edmundo R. M. (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2025)
Network slicing has been a key supporting technology for resource management in modern computer networks, from 5G to 6G and beyond. This paper summarises the thesis developed by the first author at the IC/UNICAMP. This work presents new resource management mechanisms for the dynamic network slicing allocation problem to support mobile users in 5G/edge computing infrastructures. A network simulator was developed to evaluate the proposed solutions. The simulator is available as free software and has been adopted as the validation environment by the scientific community. The results of this work indicate the positive impact of slices’ dynamic resource allocation in dealing with demand variations triggered by mobile users.